ناول ''کئی چاند تھے سر آسماں '' کے بین السطور '' مہاساخت '' لفظیات کی نشاندہی - Dr. Irm Batool; Dr. Farhat Jabeen Virk (Khayaban - خیابان, 2023)
In order to adapt the novel Kai Chaanad Thay Sar-e-Asman (The Mirror of Beauty) to the requirements of the modern era, its Vocabulary has- been thoroughly reviewed so that vocabulary can Come out with its inner making along with all the necessary references. Both dictionary and Special dictionary are used in different meanings in urdu Because the Principles of Compiling special dictionary are from the Principles of lexicography. Very different Special Dictionary includes vocabulary, compounds, terms, idioms. Related to a particular language or a particular aspect of science or art and their respective meanings are included. The Purpose of a Special Dictionary of literary texts is to analyze the words of writer or Post, especially the words of classical texts in Social, historical and cultural terms. Cultural change changes the meaning of any words. Therefore, it is important to take into account the specific words of the author while compiling special dictionary. A special dictionary gives the corresponding meaning of word as intended by the author. Another important purpose of special Dictionary is to preserve our ancient literary heritage by -translating words from ancient classical texts into “language so that easily these texts can be understood by a common reader. It is an established Principle of linguistics that language changes over change some class terms time and words change. This linguistic change comes in regional, geographical, social and class terms. Many meanings of a word are used included in the dictionary, but Special dictionary include only those meanings. Come from the Poet or writer’s Phrase.